0166 Daylight Saving Time Transitions and Admissions of Adolescents for Depressive Symptoms in an Inpatient Psychiatry Unit. (27th April 2018) - Boafo, A; Greenham, S; Robillard, R; De Koninck, J
Abstract: Introduction: Recently, it has been reported that the switch back from Daylight Saving (DST) to Standard Time (ST) in the fall was associated with significant increases in admissions for major depression in psychiatric units in Copenhagen (Hansen et al. 2017). The present study attempted to determine if this phenomenon applies to adolescent admissions for depressive symptoms (DS) to a psychiatry unit in Canada. Methods: Weekly admissions (WA) to an adolescent psychiatric unit for DS were examined from 2012 to 2017 (approximatively 400 a year for a total of 2029 admissions). Preliminary time series analyses were computed with dates synchronized to each year's DST switch dates and school periods including holiday breaks. Results: For each one of the 5 years, there were highly significant surges in admissions with the September and January school starts and a sharp reduction in the Christmas-New Year breaks. Actually WA were significantly higher during school periods (mean=8.8) than during off school periods (mean= 6.4, t -test, p<.0001). In contrast with previous findings with adults, there was on average a noticeable but not significant reduction in WA in the weeks following the Fall switch back to ST. Conversely, there was a non-significant increase in admissions following the spring return to DST. Conclusion: The surge in admissions and their higher levels with schooling is not surprising given the stress involved. The trend towards a decrease following the fall switch to ST needs further exploration as it may be that the additional hour of sleep more than compensates for the reduction in afternoon light. As for the trending surge in the spring switch to DST it may be due to the potential loss of one hour of sleep consistent with the recent observations that sleep deficits are an important contributor to depression in adolescents (Tochigi et al., 2016) and/or to the return to school after the one week March Spring break that coincides. Support (If Any):